2000
DOI: 10.1063/1.1286262
|View full text |Cite
|
Sign up to set email alerts
|

On the dispersion managed soliton

Abstract: We review various methods used to study the dispersion managed soliton for nonlinear return-to-zero pulse propagation in optical fibers. A numerical averaging method, the guiding center soliton, the variational method both with a simple and with an extended ansatz, as well as the multiscale theory are discussed and numerically compared, allowing us to show their domains of applicability. Their relative merits and demerits are then exposed. (c) 2000 American Institute of Physics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 18 publications
(16 reference statements)
0
29
0
1
Order By: Relevance
“…The propagation of solitons through optical fibers has been a major area of research given its potential applicability in all optical communication systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The field of telecommunications has undergone a substantial evolution in the last couple of decades due to the impressive progress in the development of optical fibers, optical amplifiers as well as transmitters and receivers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation of solitons through optical fibers has been a major area of research given its potential applicability in all optical communication systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The field of telecommunications has undergone a substantial evolution in the last couple of decades due to the impressive progress in the development of optical fibers, optical amplifiers as well as transmitters and receivers.…”
Section: Introductionmentioning
confidence: 99%
“…When the data rate is quite high, soliton transmission can be used. It allows the exploitation of the fiber capacity much more, but the NRZ signals offer very high potential especially in terms of simplicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…It allows the exploitation of the fiber capacity much more, but the NRZ signals offer very high potential especially in terms of simplicity [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, these papers merely point out the existence of the bi-solitons under special conditions. In this paper, a steady pulse with two main lobes, or bi-soliton, obtained by the averaging method [13,14] is reported for the first time. In addition, it is shown that this bi-soliton exists in a relatively wide parameter region.…”
Section: Introductionmentioning
confidence: 99%